Career choice in Singapore's uniformed services - Kan, Timothy Soon Hong (2019)
As a small city-state with limited resources, Singapore utilizes uniformed services comprising regulars and enlisted male conscripts as part of her defense force. With projected manpower reductions due to an ageing population and declining birth rates, it is critical for Singapore’s uniformed services to maximize efforts in the retention and recruitment of regulars and non-regulars to maintain its operational capabilities. This study aims to contribute to the retention and recruitment efforts by studying the factors that affect the intentions of regulars, non-regular males and non-regular females to work in Singapore’s uniformed services. 253 subjects were recruited to participate in a cross-sectional survey study. Their career intentions, motivation to serve, occupational identity, social influence and perceived person-environment fit were measured. Structural equation modelling was used to test the structural framework and develop unique parsimonious models of career intentions and its antecedents for the three groups of participants (i.e. regulars, non-regular males and non-regular females). Results supported three underlying factors of MTS, namely, affective, normative and transactional MTS. Relationships between career intentions and its antecedents varied for each of the groups while perceived person-job fit predicted career intentions and affective MTS for all three groups. Findings are discussed in terms of their implications to the recruitment and retention efforts of Singapore’s uniformed services. Overall, this study highlights the need to study the factors influencing career intentions of regulars, non-regular males and non-regular females.